Adab kepada Ulama dalam Perspektif Hadis: Kajian Kritis terhadap Sikap Ghuluw: Etiquette Toward Islamic Scholars in the Perspective of Hadith: A Critical Study of the Attitude of Ghuluw - Syahid Nurul Yaqin; Bisri Tujang (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study aims to analyze etiquette toward ulama and examine the prohibition of ghuluw from a hadith perspective. The development of digital media and changes in religious authority have influenced public relations with religious figures and shaped patterns of adherence that are not always based on scholarly depth. This condition highlights the importance of a hadith-based framework for understanding the boundary between respect for ulama and excessive attitudes toward religious figures. This study employs a qualitative approach through library research based on thematic hadith analysis (mawḍū‘ī). Primary sources include hadith collections and classical adab literature, while secondary sources consist of scholarly articles relevant to the topic. The findings show that the Prophet’s hadiths construct a framework of proportional respect toward ulama based on their scholarly authority as inheritors of prophetic knowledge rather than personal privilege. Hadiths concerning the prohibition of ghuluw indicate concern toward excessive religious attitudes that, in some scholarly interpretations, carry theological implications. The principle of wasathiyyah may be understood as a framework for explaining a balanced relationship between Muslims and ulama.